How misinformation and mismatched expectations reduce adoption of improved seeds - Miehe, Caroline; Nabwire, Leocardia; Sparrow, Robert; Spielman, David J.; Van Campenhout, Bjorn (VoxDev, 2025)
Often presented as game-changing solutions, agricultural technologies like improved seeds or fertilisers can lead farmers to adopt one at the expense of others, only to disadopt when the expected gains, based on overly optimistic assumptions about reduced need for complementary inputs, fail to materialise.